Entrained-flow gasification of torrefied tomato peels: Combining torrefaction experiments with chemical equilibrium modeling for gasification. (15th May 2018) - Brachi, Paola; Chirone, Riccardo; Miccio, Francesco; Miccio, Michele; Ruoppolo, Giovanna
Graphical abstract: Highlights: A chemical equilibrium model for biomass gasification was developed and validated. The effect of torrefaction pretreatment on product gas quality was investigated. Ultimate analysis data of raw and torrefied feedstocks were used in the model. The influence of the gasification conditions on product gas quality is discussed. Torrefaction provides only a marginal improvement in product gas quality. Abstract: The purpose of the present study is to quantify the impact of torrefaction pretreatment on the quality of the product gas arising from the gasification with steam and steam-oxygen mixtures of non-woody biomass in high-temperature entrained flow reactors. To this aim, a chemical equilibrium model for biomass gasification was adopted, which allowed predicting the product gas composition as a function of process temperature, equivalence ratio, steam-to-biomass ratio and biomass elemental composition. A global sensitivity analysis with respect to the model input parameters was performed to assess the impact of torrefaction and gasification operating conditions on the quality of the product gas in terms of heating value and composition metrics typically adopted in the process industry (H2 /CO ratio, stoichiometric module, etc.). In particular, the gasification of raw tomato peels and related torrefied solids resulting from fluidized bed torrefaction tests performed under light (200 °C and 30 min), medium (240 °C and 30 min) and severe (285 °C and 30 min) conditions was investigated using ultimate analysis data in the model. Results of this analysis highlighted that the quality of product gas arising from the oxygen-steam gasification of torrefied and untreated tomato peels did not differ very much, although torrefied feedstocks produced more H2 and CO and less CO2 than the parent one. This suggests that, despite the significant benefits it determines in biomass feeding, grinding and storage, the torrefaction pretreatment provides only a marginal improvement in the product gas quality. Equilibrium simulations made available in the present study can be useful for a better understanding of the controlling variables that rule gasification processes in addition to act as a point of reference for more complex simulations of the high temperature entrained flow gasification of biomass with oxygen-steam mixtures.